2004
DOI: 10.1007/bf02984474
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial analysis on the short-term side effects occurring within 96 hour after radioiodine-131 therapy for differentiated thyroid carcinoma

Abstract: Significant factors influencing short-term side effects were dose per body weight and TSH values for gastrointestinal complaints, and female sex for salivary gland swelling with pain. Our preliminary experience suggests that the most frequent gastrointestinal complaints can be prevented with ramosetron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 3 publications
0
37
1
1
Order By: Relevance
“…Salivary glands are highly radiosensitive (3). Radiation sialadenitis and xerostomia have become the most frequent complication of high-activity 131 I therapy for thyroid cancer (2,(4)(5)(6)(7)(8)(9). Additionally, salivary gland injury can be observed even when the administered 131 I activity is relatively low (7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Salivary glands are highly radiosensitive (3). Radiation sialadenitis and xerostomia have become the most frequent complication of high-activity 131 I therapy for thyroid cancer (2,(4)(5)(6)(7)(8)(9). Additionally, salivary gland injury can be observed even when the administered 131 I activity is relatively low (7)(8)(9).…”
mentioning
confidence: 99%
“…Radiation sialadenitis and xerostomia have become the most frequent complication of high-activity 131 I therapy for thyroid cancer (2,(4)(5)(6)(7)(8)(9). Additionally, salivary gland injury can be observed even when the administered 131 I activity is relatively low (7)(8)(9). Recent reviews of adverse salivary effects after 131 I therapy have indicated an incidence of acute sialadenitis ranging from 24% to 67%, with chronic sialadenitis in 11%243% of those treated (2,8,9).…”
mentioning
confidence: 99%
“…In the conditions of low iodine diet, the uptake of iodine in thyroid cells is mainly related to thyroid cell differentiation and the intensity of stimulation with TSH. However, most of the patients had a very large amount of remnant radioactivity in the gastrointestinal tract (stomach and colon), most likely because the patients were severely hypothyroid (TSH ranged from 31 to 359, 162.71 ± 98.78 mIU/L) prior to radioiodine therapy, which could be associated with the delayed transit of contents through the intestinal tract (Kita et al 2004). In addition, during hypothyroidism after thyroid hormone withdrawal, renal clearance of radioiodine decreases, potentially prolonging its retention in the body (Remy et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Salivary gland dysfunction is considered to be the most common complication of RIT and occurs in 11.5%-86% cases [1,3] . In as many as 15% patients, this side effect may be permanent [2,6] . Toxicity was reported to be associated with repeated RIT administration [1,6] .…”
Section: Introductionmentioning
confidence: 99%
“…In as many as 15% patients, this side effect may be permanent [2,6] . Toxicity was reported to be associated with repeated RIT administration [1,6] . The Na/K/Cl cotransport system concentrates radioactive iodine in the salivary gland and makes the salivary glands prone to dysfunction [3,7] .…”
Section: Introductionmentioning
confidence: 99%